Research Status, Problems and Direction of Soil Organic Carbon in Zoige Peat Wetland - Ma, Chanhua; Xu, Zhengqiang (Bilingual Publishing Group, 2023)
Peatlands, as a special type of wetland, occupy only 3% of the Earth’s surface, but bear about one-third of the world’s soil carbon storage and play an important role in the global carbon cycle. The Zoige Wetland is located on the eastern edge of the Qinghai-Tibet Plateau, and its peat reserves are up to 1.9 billion tons, accounting for more than 40% of the country’s peat resources, which is an important support for China to achieve the “double carbon” goal. This paper reviews the research status and storage estimation of soil organic carbon in Zoige Wetland. The statistical results show that there is a large difference in the estimation of carbon storage in the peatland of Zoige (0.43-1.42 Pg). The reasons are mainly related to marked differences in values reported for soil densities, organic carbon levels, and accumulation rates. There are still great uncertainties in the estimation of wetland carbon stocks, and future studies should focus on reducing soil carbon sink uncertainties, climate change, the impact of permafrost melting on carbon sink functions, the impact of degraded ecosystem restoration and sink enhancement pathways, and other greenhouse gas functions. In order to accurately reveal the current situation and future trend of carbon sink in peat wetlands, a model-multi-source observation data fusion system was constructed to complement the observation shortcomings in key areas, and provide reference and support for the construction of carbon neutral ecological civilization.